The Role of Total Quality Management in Achieving Competitive Advantage: A Pilot Study at the University of Maysan - Husham Mayea Fazaa Almusaedi (HM Journals, 2022)
The concept of total quality management is one of the relatively modern management concepts that the departments of all organizations in the industrially developed countries emphasized, as well as many organizations in the developing countries and worked on applying it, including higher education institutions in order to raise the level of their performance in order to confront the forces affecting their work, including competition between Public and private universities and between national and foreign universities, the study aims to find out the effectiveness of total quality management and its role in achieving the competitive advantage of organizations.